The Interpersonal Sources of the Development of Political Images: An Intensive, Longitudinal Perspective - Baas, Larry (Operant Subjectivity, 1997)
Harold Lasswell, among others, has noted that the vague, diffuse, and distant symbols of the secondary political world are elaborated and take on personal meaning to the individual as a result of a process of displacement or projection of some image from the primary world. To examine whether such a process mediate between primary and secondary worlds, a single subject was given two separate Q samples and asked to describe her images of 25 objects as well as how these objects made her feel. The correlation and factor analysis of these data, plus lengthy interviews with her, demonstrated how the varied aspects of her political world take on personal meaning to her with respect to specific primary images. The current study is and update of the study after almost 14 years. The same subject was asked to describe many of the objects from the original study as well as other "new" primary and political objects in her life. Once again the data support the Lasswellian proposition that primary and secondary worlds are bridged by a process of displacement of primary affect. Additionally, the data allow us to see how new objects are incorporated into her world and how changes in her primary world affect her images of the secondary political world, as well as how earlier images impact ones developed later.